Primary malignant Brenner tumor of the ovary: a case report - Hao, Kun; Gao, Feng (Frontiers in Oncology, 2026)
Ovarian Brenner tumor is a rare type of ovarian epithelial neoplasm, predominantly benign, with only a minority exhibiting borderline or malignant characteristics. Malignant Brenner tumors (MBTs) resemble invasive urothelial carcinoma and often coexist with benign or borderline Brenner tumors. Clinically, they frequently present with non-specific symptoms, including abdominal pain and weight loss. We report the case of a 53-year-old female who presented with a mixed echoic mass in the left adnexa identified by gynecological ultrasound. Histopathological and immunohistochemical analyses of the resected specimens confirmed the diagnosis of ovarian MBT. The patient was subsequently referred for adjuvant treatment. This case highlights the diagnostic challenge of MBT and underscores the critical role of immunohistochemistry (positive for GATA3 and p63, negative for Pax-8) in confirming the diagnosis and distinguishing MBT from its histological mimics.